JURNAL PENGEMBANGAN MEDIA CROSSWORD PUZZLE MATERI PERUBAHAN ZAT WUJUD BENDA KELAS V SD RADEN PATAH SURABAYA - Achmad Fauzen; Anna Roosyanti; Noviana Desiningkrum (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to develop a crossword puzzle media on the material change of matter for the fifth grade of elementary school . This research is a development (Research and Development). The implementation of the media uses a pre-test and post-test control design with class V subjects at SD Raden Patah Balongsari Surabaya 2022-2023. The results of the research on the development of this crossword puzzle media were by first making the columns, then numbering each column with numbers and next to it being asked descending and ascending questions. Problem formulation 1. How is the feasibility of crossword puzzle media in terms of media format, concept, material and language aspects 2. How is the effectiveness of crossword puzzle media to teach the material of changing objects Based on the results of the media assessment conducted by 2validators, the crossword puzzle media is included in the valid category. The application of crossword puzzle media is effectively used for learning material changes in matter, it can be seen from the completeness of the classical pre-test results, which is 76.90 then after applying the crossword puzzle media it is reduced to 75.95. It shows that the crossword puzzle media is effectively used in science learning. The student's response to science learning material changes in matter of matter using crossword puzzle media was well received by class V SD Raden Patah Balongsari Surabaya